Muslim cultures of the Indian Ocean : diversity and pluralism, past and present - Pradines, Stéphane; Topan, Farouk (Exploring Muslim contexts., 2023)
Explores the role of Islam in forming and transforming interconnectivity across the Indian Ocean World from a longue duréeperspective.